Synthesis of Alumina Using Composite Fuel: Mixed Fuel Method - Saurabh Sharma; Dr Jitendra Kumar Gupta (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this paper, “Synthesis of Alumina using composite fuel was choosen, composite of two fuel types (urea & glycine) was used, along with aluminium nitrate as oxidizer, to synthesise alumina powder. Three samples with variation in fuel to oxidizer ratio were prepared, in reference to stoichiometric ratio. Samples were further characterized with respect to observation of combustion flame, XRD and SEM analysis. Here other than fuel to oxidizer ratio, effect of mixed fuel on solution combustion and product obtained was also a parameter. Results obtained are in good agreement with available literature and almost as expected, from application point of view. Additionally, mixed fuel shows considerable changes in combustion parameters.